Metody bayesowskie szacowania wartości rezerwy szkodowej - Jadamus-Hacura, Maria (Bayesian Estimation of Outstanding Claims Reserves, 2006)
This paper examines Bayesian model for loss reserving inspired by a consideration of some of the methods appearing in the traditional chain ladder literature. This includes possible order restricted hierarchical Bayesian model for the year over year development factors. Described Bayesian model can be implemented using Markov chain Monte Carlo (MCMC) methods and can serve as a starting point for more advanced models. This paper describes its implementation in WINBUGS (a specialized software programme for MCMC simulations).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 286-292